FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN SEKTOR KONSUMEN PRIMER - Fernandez, Felix; Ekadjaja, Agustin (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to examine the effects of profitability, leverage, and firm size on firm value. The sampling approach in this study used non-probabilistic sampling with purposive sampling methods as the sampling method. The study used 174 samples from 58 primary consumers companies listed on the Indonesian Stock Exchange from 2019 to 2021. Data for this study are taken from financial reports and processed in Microsoft Excel and SPSS programs using multiple regression analysis. The results of this study show that profitability, leverage and firm size also affect firm value. In some cases, profitability, leverage and company size can have a significant positive impact on company value.